Cellulose and Soy Proteins Based Membrane Networks. Issue 1 (23rd August 2013) - Zhu, Yidan; Douglass, Eugene; Theyson, Tom; Hogan, Robina; Kotek, Richard; Bowman, Christopher N.; Horkay, Ferenc
Summary Using the novel ethylenediamine/potassium thiocyanate (ED/KSCN) solvent system developed in our labs, a simpler, environmentally friendlier method was developed to produce membranes using cellulose, proteins, and other polymers. In contrast to current industrial methods that use processes that are relatively expensive with toxic or dangerous solvents, the new system eliminated majority of those concerns. In this study, soy protein concentrate and cellulose was used to develop a nonporous composite membrane with good physical properties. Glutaraldehyde was applied as the crosslinking agent to stabilize the molecular network structure of the blended membranes. Results showed that nonporous membranes were produced that were strong, flexible, and the exposure to the crosslinking agent shown structural and thermal improvement of the network membranes. This resulting blend of biopolymer membranes with improved physical abilities can be useful for food packaging, filtration systems, or even medical applications.